PHENOMENOLOGY STUDY : HIV PATIENT EXPERIENCE TRANSVESTITE TO FULFILL SPIRITUAL NEED - chaterina Janes Pratiwi; Ika Ainur Rofi'ah; Arief Andriyanto; Enny Virda Yuniarti; Agung Waluyo; Sri Yona (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2019)
The prevalence of HIV cases increases significantly in the vulnerable population; it is Transvestite. The high prevalence of HIV in transgenders requires treatment and treatment services. However, until now the transgender community is a group that is often not served in various health facilities. Transvestite identity intersections produce unique life experiences, such as multiple identities and spiritual identities. The purpose of the study was to explore the experience of transgender HIV patients when hospitalized in fulfilling spiritual needs. Research method with qualitative design phenomenology study approach. This study involved 12 transvestite participants who had been hospitalized because of HIV positive. Retrieving data using in-depth interviews, data analysis using Colaizzi. The results of the study found four themes namely (1) Spiritual according to HIV patients transvestites means believing in the existence of God; (2) Be grateful for the conditions they have; (3) get closer to God by doing good things; (4) Poor nurse services for transgender HIV patients.